Análisis Financiero al Cuerpo de Bomberos del Cantón Catamayo, provincia de Loja, período 2020-2021 - Diaz Ordoñez, Cinthya Lizbeth (2024)
Financial analysis allows the institutions to have a key diagnosis in their operational activities, determining the economic conditions in the present with the management of financial resources available to predict the future of the company. The purpose of the research is to analyze the financial statements of the Fire Department of the Catamayo canton, which belongs to the province of Loja, by conducting vertical and horizontal analysis using economic indicators for the period 2020-2021. The research was based on a mixed-method approach, with a non-experimental design of exploratory level with descriptive scope, using deductive and scientific methods. The techniques and instruments for collecting information were an interview with the accountant to obtain the institution's background and direct observation of the financial statements. The results determined an increase in advances of funds since in 2020, it consisted of 0.0010% and in 2021 with 0.90%, the consequence of this increase is that the institution was not able to make payments in the determined period, these advances were requested by the firefighter personnel. There was a decrease in cash and cash equivalents, which represented 60.58% in 2020 and 46.84% of current assets in 2021, this was due to the cancellation of salaries of operational and administrative personnel. Most of the incomes help to ERRSSA's contributions in Catamayo value which increased from $ 63,863.81 of 22.27% of revenues in relation to the years 2020- 2021. Regarding the application of financial indicators are within the established standards without affecting the fulfillment of its activities in financing.